Electrohydropulse technology of destruction and crushing of natural stones at different parameters - B.A. Akhmadiev; A. Tatybekov; N.N. Shuyushbayeva; N.K. Tanasheva; G.S. Altayeva; M. Stoev (Қарағанды университетінің хабаршысы. Физика сериясы)
The aim of the study is to develop scientific and practical principles of implementation of energy saving heat pump technology for heat and cold supply to residential, public and industrial premises on the basis of alternative and renewable sources of energy. One of the effective methods to generate heat from groundwater by means of heat pump technology is the use of wells for consolidation of heat exchange elements produced by drilling. Fundamentally new innovative method of making wells is electro-hydraulic drilling, when electrical energy directly in the bottomhole transforms into mechanical energy of shock waves that can break up rocks. This paper describes the results of studies of the impact of electro-hydraulic pulse on hard and superhard rock minerals. The quantitative dependency, characterizing the beginning of the process of destruction of rocks of various thickness depending on the number and energy of discharges was defined. The experimental work proved the possibility of achieving higher drilling speeds compared to those at conventionally used plants. The electric pulse destruction is implemented without using a drilling bit, it does not require special tightness of electrodes to bottomhole surface with considerable force; therefore, the wear of the electrodes at electrohydraulic pulse drilling is relatively minor.